2005
DOI: 10.1016/j.pain.2005.06.031
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of duloxetine in the treatment of women with fibromyalgia with or without major depressive disorder

Abstract: This was a 12-week, randomized, double-blind, placebo-controlled trial to assess the efficacy and safety of duloxetine, a selective serotonin and norepinephrine reuptake inhibitor, in 354 female patients with primary fibromyalgia, with or without current major depressive disorder. Patients (90% Caucasian; mean age, 49.6 years; 26% with current major depressive disorder) received duloxetine 60 mg once daily (QD) (N=118), duloxetine 60 mg twice daily (BID) (N=116), or placebo (N=120). The primary outcome was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
321
4
20

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 423 publications
(359 citation statements)
references
References 18 publications
14
321
4
20
Order By: Relevance
“…As noted earlier in this article, patients and their families should have their expectations managed on initiation of any therapy, with PCPs reiterating that although medications cannot cure the underlying disease, medications can improve symptoms and function. [31][32][33][34] Pregabalin is an alpha 2 delta calcium channel ligand; duloxetine and milnacipran are serotonin and norepinephrine reuptake inhibitors (Table). Alpha 2 delta calcium channel ligands are thought to act in part by reducing the activity of excitatory neurotransmitters (eg, glutamate), whereas serotonin and norepinephrine reuptake inhibitors act largely by increasing norepinephrine and serotonin and thereby increasing activity in the descending inhibitory pain pathways.…”
Section: Apply a Multimodal Treatment Approachmentioning
confidence: 99%
“…As noted earlier in this article, patients and their families should have their expectations managed on initiation of any therapy, with PCPs reiterating that although medications cannot cure the underlying disease, medications can improve symptoms and function. [31][32][33][34] Pregabalin is an alpha 2 delta calcium channel ligand; duloxetine and milnacipran are serotonin and norepinephrine reuptake inhibitors (Table). Alpha 2 delta calcium channel ligands are thought to act in part by reducing the activity of excitatory neurotransmitters (eg, glutamate), whereas serotonin and norepinephrine reuptake inhibitors act largely by increasing norepinephrine and serotonin and thereby increasing activity in the descending inhibitory pain pathways.…”
Section: Apply a Multimodal Treatment Approachmentioning
confidence: 99%
“…But one should consider that the selective action of an antidepressant on the central nervous system does not necessarily resulting a selective response (42). Similarly, several studies have suggested that mirtazapine, venlafaxine, duloxetine , milnacipran also act to enhance the activity of central NA and 5-HT neurones and might be useful in the treatment of pain in both humans and/ or animals (43)(44)(45)(46)(47)(48)(49)(50)(51)18,10).…”
Section: Discussionmentioning
confidence: 99%
“…46 Three trials concerning Duloxetine in FMS were involved. 28,29,31 The response rate was defined as a 50% reduction in the average pain score from baseline to endpoint. The Number Need to Treat (NNT) compared with the placebo was 6.4 (4.7 to 9.9).…”
Section: Efficacymentioning
confidence: 99%